The usage of information systems, factors affecting the usage and its impact on financial audit process and on e-fraud detection - Katamba, Asha Baleche (2019)
This study is driven by the motive to understand the usage of IS by external auditors amid their clients’ move into e-business platforms in processing and storing information. It is reported that the e-business models have improved business availability, accessibility, cost and time, but have also increased complexities, chances for fraud, errors, theft, damages and other irregularities. Specifically, electronic-based transaction fraud can easily be committed by internal or external system experts and might stay for a long time undetected, hence increasing the chances for audit risk. On the contrary, there are IS tools that can help auditors to examine clients’ financial information where it is difficult to do so manually and also to detect fraud. It will therefore be critical and essential to understand the extent of use of IS by external auditors when auditing their computerised clients. Most studies in this area have either focused on internal auditors or in developed countries making external auditors and emerging markets especially those in Africa to be unrepresented. Yet, advances in technology are spreading across the African countries; and audit firms in these countries are anticipated to utilise technology for various productivities. For Tanzania, this will be the first study to investigate the extent of use of IS among external auditors as e-business is gaining momentum in the country and also electronic-based fraud were reported on the rise. With that, the study explored the extent of IS usage among external auditors, factors influencing the usage of IS and the impact of IS usage on the audit process and on e-fraud detection. A concurrent mixed method approach was espoused where interview was the main enquiry tool and surveys a secondary enquiry. The unified theory of acceptance and use of technology (UTAUT) was adopted and modified with inclusion of external factors to understand the factors for IS usage among external auditors. Data were collected in two phases. In the first phase, the study interviewed 13 external auditors at management level from audit firms that were allowed to audit banks and financial institutions. In the second phase, questionnaires were sent out with an intention to obtain a larger sample in understanding the motivation for IS usage and to complement the interview findings. SPSS and NVIVO were used to analyse the data from surveys and interviews respectively. The interview data were analysed in themes while the survey data were analysed in demographics, percentages, frequencies, means, standard deviations and inferential statistics such as EFA and regression. The findings revealed that external auditors in Tanzania make use of office automation technologies (Word Processing, Excel; Electronic working papers), audit automation technologies (ACL, IDEA, GAM-X, PCAS, Auto-Audit, SASoft, AS2; Excel), Networking and data transfer (Teammate, EMS, E-mails; work related-messengers) and Ecommerce technologies/Intruders detection technologies (Ethical hacking tools). On the factors for IS usage, the interview findings showed that external factors were the strongest drivers that inspired auditors to increase the use of IS namely; clients’ related factors and the audit oversight body. Meanwhile, the survey results also showed that clients’ factor was the most significant predictor that influenced auditors to increase the use of IS and efforts expectancy. Furthermore, the findings revealed that IS had improved the audit process from documentation, audit testing and reporting as it enhanced auditors to adhere to audit standards and in assessing risks better than manual processes. Lastly, IS tools enabled auditors to detect e-fraud that occurred electronically. The use of ethical hacking tools through penetration testing was one of the techniques that auditors employed by detecting unauthorised access to the entity’s system. As a result, it increased detection rate, deterred new fraud from occurring and reduced financial statement frauds. The types of e-fraud that were discovered using IS tools include IT related faults, illegal access to the entity’s system by a terminated senior employee, stealing passwords, opening fake accounts and transferring cash therein, transferring cash in small denominations from multiple customers, mobile banking sim-swap fraud and fake hotel bookings among others. The findings of the study open an understanding on the impact of IS usage among external auditors in Tanzania, which has useful insights for developing countries, accounting professionals, software developers, investors, accounting oversight bodies and scholars. The study is expected to foster IS usage in auditing so as to increase the level of audit assurance in computing business platforms.